Advanced glycation end product intake during pregnancy and offspring allergy outcomes: A Prospective cohort study. Issue 11 (15th October 2021) - Venter, Carina; Pickett, Kaci; Starling, Anne; Maslin, Kate; Smith, Pete K.; Palumbo, Michaela P.; O'Mahony, Liam; Ben Abdallah, Miriam; Dabelea, Dana
Abstract: Background: Associations have been shown between concurrent assessment of dietary intake of advanced glycation end products (AGEs) and childhood allergic outcomes. We examined the association between maternal AGEs intake and development of offspring asthma, wheeze, atopic dermatitis, allergic rhinitis and food allergies, and sought to determine whether the intake of AGEs was associated with cord sera cytokines/chemokines. Methods: Pregnant women ≥16 years were recruited in the Healthy Start study, a prospective pre‐birth cohort from Colorado ( N = 1410). The analysis included 962 dyads with adequate diet (≥2 recalls) and allergy outcome details. AGEs intake was estimated for each mother by matching intakes reported using 24‐h dietary recalls during pregnancy to a reference database of commonly consumed foods' AGEs values. Child diagnoses of asthma and allergies up to 8 years were obtained from electronic medical records. Cord sera cytokines and chemokines were analysed in a subset ( N = 462) of children. Results: The median [IQR] AGEs intake for the overall sample was 11, 919 kU/day [8293, 16, 573]. Unadjusted analysis showed a positive association between maternal AGEs intake in pregnancy and rhinitis up to 8 years of age (HR = 1.03; 95% CI: 1.01, 1.06), but the association was attenuated and no longer significant in adjusted models (HR = 1.01; 95% CI: 0.98, 1.04). Both adjusted and unadjusted models showed no associations between AGEs intake in pregnancy and any of the other outcomes ( p > .05). There were no significant associations between any cytokine or chemokine measured and AGEs intake or any of the outcomes studied ( p > .05). Conclusion: The study showed that maternal AGEs intake was not associated with offspring asthma and allergy outcomes. AGEs exposure during pregnancy may not have the same impact on child development as postnatal exposure. Abstract : Background: Consumption of foods containing advanced glycation end products (AGEs) in childhood has been associated with allergy outcomes in children. Immunological data also indicates an association between AGEs and stimulation of an atopic phenotype. Results . Our study showed a lack of association between maternal intake of advanced glycation end products in pregnancy, cord blood cytokine and chemokine levels and offspring allergy outcomes. Our study indicates that AGEs intake by pregnant women may not be associated with offspring allergy outcomes.